Honey's new friend - Mongredien, Sue (London : Stripes, 2011)
Ella loves her gorgeous kitten, Honey, but Misty, the family's much older cat, isn't so keen. Honey likes to play, while Misty prefers peace and quiet, and soon the two cats are at war. Will Honey and Misty ever be friends?
Keywords: Children's stories; Animal fiction